ok i saw how u got -4 what do u do with the second equestion
Follow Math Help Forum on Facebook and Google+
Originally Posted by daniel323 ok i saw how u got -4 what do u do with the second equestion Nothing. Now we have the equations: -2y = 2x - 4 y = -2x + 6 So add them: (-2y + y) = (2x - 2x) + (-4 + 6)
i got 2
Originally Posted by daniel323 i got 2 How did you get 2? You need to slow down. Try solving one more time.
is in it 2(1)-2(1)+(-4+6)=2 did imiss something
-2y = 2x - 4 y = -2x + 6 So add them: (-2y + y) = (2x - 2x) + (-4 + 6) -y = 2 => y =-2. So, (-2) = -2x + 6 => x=4 The answer is (4,-2).
View Tag Cloud